2011
DOI: 10.1105/tpc.110.081943
|View full text |Cite
|
Sign up to set email alerts
|

The Plant Cuticle Is Required for Osmotic Stress Regulation of Abscisic Acid Biosynthesis and Osmotic Stress Tolerance inArabidopsis 

Abstract: Osmotic stress activates the biosynthesis of abscisic acid (ABA). One major step in ABA biosynthesis is the carotenoid cleavage catalyzed by a 9-cis epoxycarotenoid dioxygenase (NCED). To understand the mechanism for osmotic stress activation of ABA biosynthesis, we screened for Arabidopsis thaliana mutants that failed to induce the NCED3 gene expression in response to osmotic stress treatments. The ced1 (for 9-cis epoxycarotenoid dioxygenase defective 1) mutant isolated in this study showed markedly reduced e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
128
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(132 citation statements)
references
References 76 publications
1
128
0
3
Order By: Relevance
“…In addition to the direct effects of epidermal traits on water balance, the permeability of the cuticle has also been shown to affect stress defenses through influencing the hormonal response. Wang et al (2011) has reported that osmotic stress-induced ABA biosynthesis and osmotic stress tolerance were impaired in cutin mutants of Arabidopsis. This implies the possibility that the thin and permeable cuticle of Cappelle Desprez and the low level of stress defense in this cultivar (see below) are not just parallel traits formed during evolution, but might also have a functional connection.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the direct effects of epidermal traits on water balance, the permeability of the cuticle has also been shown to affect stress defenses through influencing the hormonal response. Wang et al (2011) has reported that osmotic stress-induced ABA biosynthesis and osmotic stress tolerance were impaired in cutin mutants of Arabidopsis. This implies the possibility that the thin and permeable cuticle of Cappelle Desprez and the low level of stress defense in this cultivar (see below) are not just parallel traits formed during evolution, but might also have a functional connection.…”
Section: Discussionmentioning
confidence: 99%
“…The outer layer of the cutin is covered with cuticular wax, a complex of C 20 to C 60 aliphatics, aldehydes, ketones, and wax esters, coating the outermost surface of the plant body (Pollard et al, 2008). A series of Arabidopsis mutants defective in cuticle synthesis and secretion show the biological roles of cuticles as a barrier to biotic or abiotic stresses, osmotic stress, water loss, and damage from UV radiation, and in preventing the fusion of leaves and floral organs (Yephremov et al, 1999;Pruitt et al, 2000;Krolikowski et al, 2003;Aharoni et al, 2004;Kurdyukov et al, 2006;Bessire et al, 2007;Shi et al, 2011;Wang et al, 2011). Some mutants are known to be involved in petal morphogenesis: Lack of nanoridges of petals, due to a mutation in DEFECTIVE IN CUTICULAR RIDGES (DCR, encoding a BAHD acyltransferase), CYP77A6 (cytochrome P450 family), GLYCEROL-3-PHOSPHATE ACYLTRANSFERASE6 (GPAT6), or PERMEABLE CUTICLE1 (PEC1), result in increased permeability of petals to a dye and cause organ fusion (Li-Beisson et al, 2009;Panikashvili et al, 2009;Bessire et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent reports indicate that the relationship between ABA and cutin is complex, and ABA biosynthesis and signaling are impaired in mutants with disrupted cutin biosynthesis, suggesting that cutin components may be involved in mediating osmotic stress signaling (Wang et al, 2011). In addition, the transcription factor NF-X LIKE2, which binds to the promoters of a cutin-related gene and a transcription factor regulating cutin formation (Lisso et al, 2012), suppresses ABA accumulation and ABA responses, possibly to avoid osmotic stress response under normal conditions (Lisso et al, 2011).…”
mentioning
confidence: 99%